Myxedema Coma Associated with Macroprolactinoma: Case Report and Review of the Literature. (28th April 2022) - Omoniyi, Elizabeth Jasola; Robbins, Richard J.
Abstract : Myxedema coma is a rare life-threatening presentation of severe hypothyroidism associated with a high mortality rate. Although most cases are due to primary thyroid failure, a minority have central hypothyroidism as the underlying cause. We report the case of a 69-year-old man who presented with obtundation, hypoglycemia, and hyponatremia. The patient's initial thyroid-stimulating hormone (TSH) was within normal limits. Subsequent evaluation revealed critical anterior pituitary insufficiency due to a macroprolactinoma and a diagnosis of myxedema coma after appropriate workup The finding of a normal serum TSH should not eliminate the possibility of myxedema coma.